The Effectiveness of Warm Compresses and Tepid Sponge Baths on Body Temprature in Toddlers Who Have a Fever on the First Day - Sukmandari, Ni Made Ari; Triana, Komang Yogi; Sukriyanti, Putu Ari (Poltekkes Kemenkes Surabaya, 2025)
Toddlers are susceptible to fever because their immune systems are immature. Non-pharmacological managements, such as warm compresses and tepid sponge baths, are commonly used to reduce fever. This study aimed to determine the effectiveness of warm compresses and tepid sponge baths in lowering body temperature in toddlers on the first day of fever. A quasi-experimental pretest-posttest non-equivalent control group design was used, involving 30 toddlers at TK II Udayana Denpasar Hospital. Respondents were selected through purposive sampling and divided into two groups: tepid sponge (n=15) and warm compress (n=15). Subjects belonging to the intervention group were administered tepid sponge baths, and subjects in the control group were applied warm compresses. Each group was given 20 minutes of treatment using lukewarm water with a temperature no higher than 43°C. Body temperature was measured using a calibrated digital thermometer before and after the intervention. The data were analyzed using paired t-tests for within-group differences and independent t-tests for between-group comparisons. Both interventions significantly reduced body temperature in toddlers with fever on the first day (p=0.001). The average temperature decrease in the tepid sponge group was 1.14°C (p value 0,001), slightly higher than the temperature drop in the warm compress group, which is 0.99°C (p value 0,001). Statistical analysis showed a significant difference in effectiveness between the two interventions (p value 0.001), with tepid sponge being more efficacious. Tepid sponge baths are more effective than warm compresses in reducing fever in toddlers on the first day. Nurses are encouraged to apply tepid sponge therapy as an alternative to pharmacological interventions to minimize the side effects of antipyretic drugs.